Factors Affecting Banking Policies and Solutions for Banks in Agricultural Development in Vietnam - NHI, DUONG THI AI; HUY, DINH TRAN NGOC; DAT, NGUYEN VAN (The journal of contemporary issues in business and government, 2021)
In this study we will categorize both macro factors and micro factors that affect banking policies in agricultural development in emerging market such as Vietnam. We use qualitative analytical methods including synthesis and inductive methods, together with statistic data analysis. Our study shows results that agricultural development is much affected by macro factors such as GDP growth, land area and inflation and micro factors effects such as advice from experts and hi-tech application. Then, we also present results for bank policies for agricultural development on the country. Last but not least, we believe these findings could be used by banks, companies and borrowers in agriculture.